Retaining Teaching Capacity in African Universities : Problems and Prospects - Blair, Robert; Jordan, Josephine (World Bank, Washington, DC, 2012)
A project was carried out to obtain information on academic staffing in seven African universities, and to analyze the factors influencing academic staff to leave universities in Africa. The report provides detailed analysis and comment on the data, and makes suggestions and recommendations for improvement and policy interventions. The essential factors for improved staff capacity are identified as economic growth and revival, greater autonomy for universities, and the development of diversified sources of funding so as to remove the total dependence of universities on governments for funding. A wide range of staffing policy options are suggested, with the only viable way forward possibly being a "trade-off" between high, competitive salaries, or maintaining existing conditions which provide good leave and travel benefits (in practice as well as theory), a relaxed working environment, and a general lack of accountability. Strong leadership is essential, and reinforced and restructured university personnel offices and programs are crucial. The research environment is vital for viable academic staff recruitment and retention, particularly at the more senior levels, and a number of policy options for the achievement of an improved research environment are proposed. Other areas requiring attention for successful staff retention, in addition to salaries, are a means to obtain housing and vehicles, and an urgent improvement in university facilities.